Oxidation-dominated wear behaviors of carbide-based cermets: A comparison between WC-WB-Co and Cr3C2-NiCr coatings. Issue 17 (1st December 2019) - Wang, Haibin; Yan, Xifeng; Zhang, Hannah; Gee, Mark; Zhao, Chong; Liu, Xuemei; Song, Xiaoyan
Abstract: A WC-40WB-12Co coating has been developed and demonstrated to have comparable oxidation resistance, remarkably enhanced hardness (over 2 times higher) and improved wear resistance (2–4 times higher) than the widely used Cr3 C2 -25NiCr coating at elevated temperatures. Wear failure of Cr3 C2 -NiCr coating was dominated by severe subsurface cracking due to oxidation and its poor high-temperature mechanical properties. By contrast, in the WC-WB-Co coating, the thin oxide scale formed on the surface increased lubrication and hindered further oxidation. The WC-WB-Co coating provided strong mechanical support for the oxide layer. The coating thereby achieved an outstanding high-temperature wear performance. Based on detailed comparisons, the wear mechanisms of these carbide-based cermet coatings at elevated temperatures were proposed.